(untitled) (Innovative professional education, 2024)
The section examines the necessity of developing digital platforms for professional training, which is relevant in the context of globalization and technological innovations. The authors focus on the technical aspects of evaluating such platforms, particularly their functionality, reliability, and effectiveness. Key criteria highlighted include system architecture, the use of containers such as Docker, user interface (UI), and user experience (UX). The article also emphasizes the importance of adaptive design, analysis of user needs, and inclusivity of the platform, making learning accessible to a broad audience. The primary focus is on creating conditions for effective and convenient learning that opens up education to various user groups, ensuring scalability and flexibility of educational resources.